Nanoparticles in Cancer Treatment: A Narrative Review: Nanoparticles in Cancer Treatment: A Narrative Review - Hassan, Taimoor; Huang, Xiaojia; Zhou, Chao; Khan, Muhammad Sikander Ghayas; Saeed, Sana (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
Nanoparticles have revolutionized the world with their enormous blessings specifically in cancer treatment. In past, conventional chemotherapy was the primary choice of treatment for patients. However, chemotherapeutics also had several pharmaceutical limitations such as stability, drug-drug interaction, drug resistance, and aqueous solubility. Reciprocally, dose curbing toxicity is significant with non-specific toxicity to healthy cells, loss of appetite, hair loss, peripheral neuropathy, vomiting, muscular fatigue, and diarrhea being the typical adverse effects. The introduction of multi-drug resistance (MDR) also posed a great threat for successful cancer treatment, whereby the tumor cells became resistant to many of the chemotherapeutic agents used. Nanotechnology-based novel chemotherapy opened a new horizon for the treatment of cancer. Particularly, nanoparticle-related medication is a highly potential newcomer for curtailing systemic toxicity via producing functionalized particles for specific treatment. It is also an alternative to circumvent multidrug resistance for possessing an ability to bypass the efflux mechanism correlated with this phenotype. Besides having various advantages in treatment, nanoparticles are also playing a key role in diagnostic entities. This paper aims to specifically outline the role of nanotechnology which it is playing in today’s era in the diagnosis and treatment of cancer with contemporary knowledge. To assess the role of nanoparticles in cancer treatment, this review analyzed all articles published from 2002 to 2021 in both Local and foreign journals. The article’s inclusion criteria were based on the article which contained relevant data regarding applications of nanoparticles in cancer treatment. Articles with copyright, irrelevant information, and lacking the full text were excluded. This paper will highlight the breakthrough, impediments, and prospects of nanoparticles in cancer treatment with an updated review.